Agency cost of debt: evidence from Kansas farm operations. Issue 1 (2nd May 2017) - Brewer, Brady; Featherstone, Allen M.
Abstract : Purpose: The purpose of this paper is to examine how debt affects the cost structure of a farm. Agency costs arise when stakeholders of a farm manage their farm differently to obtain debt which results in inefficiencies. These inefficiencies cause a farm to deviate from cost minimization strategies. Design/methodology/approach: This study uses the non-parametric technique of data envelopment analysis. Through this method, a non-stochastic cost frontier is constructed where all farms must lie on or above the frontier. This allows for the analysis of how debt affects the shape of the cost frontier and for how debt affects deviations away from cost-minimizing strategy. The shadow costs of the debt constraints in the linear programming problem are used to analyze the effect of debt at the cost frontier while a series of Tobit models are estimated to examine the effect of debt on deviations away from the frontier. Findings: The findings of this paper support the existence of agency costs associated with debt for Kansas farms. The addition of debt and capital constraints lowered the minimum cost frontier increasing the average efficient cost under variable returns to scale. However, for those farms on the frontier, the shadow cost of debt was negative meaning an increase in debt would lower the overall variable cost. The increase of debt was found to be negatively correlated to the efficiency score of the farms. Originality/value: This paper provides value by supporting the existence of agency costs which has been disagreed upon in the literature and also providing new insights for how to analyze agency costs. Since debt was found to have a negative shadow value for those farms on the frontier but negatively correlated with efficiency scores, this suggests that agency costs affect firms differently depending on where the farm is on the cost frontier.